PARTICIPATIVE DECENTRALIZED CLOUD STORAGE SYSTEM UTILIZING BLOCKCHAIN - Fadlurohman, Akmal
The steady and fast development of information technology has changed the way people are using their personal computer in daily life. The activities such as taking pictures or recording videos generate a lot of digital data in the form of files whose numbers are growing continuously. Cloud storage services as an online storage media may be utilized by those people for keeping their personal files and data. The facility and ease of use provided by such services are increasing the percentage of the services adoption by many of the personal computer users around the world. In the period of the year 2014-2018, the number of personal cloud storage service users has grown by 40% and is continuously ever growing. The increase of the number of users requires the provider of cloud storage services to provide more and more data center facilities to tend to the market needs. The fees of cloud services tend to be expensive because the cloud storage users are being charged the cost of building and maintaining these data canter facilities. In the other side, many of the personal computer users are having unused or underutilized storage on their devices. These storages could be further utilized and produce more benefits by renting it out to other users. This final work has the focus on developing a system that may be used for personal computer users to rent out their underutilized storage devices and to rent storage spaces for keeping personal files. The many users under this motives participate in the system and form a distributed decentralized peer-to-peer cloud storage network. Users who need cloud storage service for keeping their personal files are able to rent storage spaces from other users in the network. This business process works in a peer-to-peer way and is executed on-chain at the blockchain of the system. The blockchain technology is applied to help record all the transactions that happen within the network as a result of the execution of various business processes of the system that includes registration of storage space for rent out, renting storage spaces from other users, and the deposit and withdrawal of cryptocurrency balance used as the currency or payment item for the services being traded so that the system is able to assures the integrity of transactions and the accountability of business processes. The blockchain also supports the peer-to-peer model of the system because of its decentralized nature. The participative decentralized cloud storage utilizing blockchain system prototype in overall was able to solve the problem of the utilization of unused storage spaces on personal computers. The prototype was able to be used by storage owners to participate in renting out their storage devices to become a cloud storage. The prototype was also able to be used by users who would like to keep their personal files in the system and rent the necessary storage spaces from other users in the system. The business processes of the system were all able to work in a peer-topeer way and executed on-chain as smart contracts at the blockchain of the system. The transactions resulted from the business processes were also able to be recorded in the blockchain successfully.